1634: the ram rebellion ebook - Flint, Eric (Ring of Fire: Assiti Shards, 2019)
The Great Revolt is On! Europe, 1634. With the example of future Grantsville, U.S.A., a small town thrown back in time by a cosmic accident, a peasant revolt becomes a revolutionary movement. You're from the future. You want the serfs to liberate themselves-but you also know what a bloodbath the French Revolution became. Avoiding that possibility will take all American horse-trading diplomacy you can muster. The stakes: an explosion that could cover half the continent in blood! Alternate history master Eric Flint and exciting newcomer Virginia DeMarce fire another exciting volley in Flint's engrossing "Grantsville" chronicles. At the publisher's request, this title is sold without DRM (Digital Rights Management).